ANALISIS TINGKAT KRIMINALITAS DI INDONESIA DENGAN HIERAKI CLUSTER MENGGUNAKAN METODE WARD: ANALYSIS OF CRIMINALITY RATES IN INDONESIA WITH CLUSTER HIERARCHY - Alfikri, Gilang Nur; Suprianto, Andi (JURNAL REKAYASA INFORMASI, 2023)
In 2021, there has been a spike in crime cases which has caused concern among the public. In response to this situation, a study was carried out with the aim of identifying crime rates in all provinces in Indonesia and grouping them according to certain categories. The approach used in this study involves the Hierarchical Cluster technique with the Ward method, which will analyze datasets covering 34 provinces in Indonesia. This grouping will be run through the Jupyter Notebook environment using the Python programming language. The main result of this study is to provide insight into the level of security and the overall situation in terms of order in each province in Indonesia Keyword: Criminality, Hierarchical Cluster, Indonesia, Ward, Jupyter Notebook